The image of women in digital sports press: analysis of the covers of as.com and marca.com - Mayoral Sánchez, Javier; Mera Fernández, Montserrat (CIC. Cuadernos de Información y Comunicación, 2017)
This paper analyze the image of women in the two most widely read sports digital media Spain. On the covers of as.com and marca.com 5,105 photographs have been counted. Only in 2.45% of the images analyzed we found a woman athlete. In six out of ten photos we see some sort of sexual connotation.
Keywords: Sports information; Women and Sport; Digital Journalism; Sexism; Information on Gender.